Preliminary Study on the Effect of Nitrogen Fertilisation on Phytochemical Content Quality of Gynura procumbens - Mohamad Fhaizal Mohamad Bukhori,; Hawa Jaafar,; Ali Ghasemzadeh,; Uma Rani Sinniah,; Gayatri Karipaya, (Tropical Life Sciences Research, 2021)
The study was carried out to examine the effects of nitrogen (N) fertilisation on phytochemical content quality, to determine types of phytochemicals compositions, and to establish phytochemicals marker compounds in Gynura procumbens. In this two factors study, three stages of harvesting (H) time and three rates of N were laid out according to Randomised Complete Block Design (RCBD). Physiological and biochemical attributes were recorded to exhibit the trend for plant quality. The results showed that, N has affected phytochemical content significantly (p < 0.05) with stronger effect on physiological and biochemical attributes (p < 0.01). The results suggested that 0 and 90 kg/ha N, respectively are highly and least effecting the Photo, Cond, TChlC, TCC, TPrc, TLiC, TPC and TFC. Kajian ini dijalankan untuk mengkaji kesan baja nitrogen (N) terhadap kualiti kandungan fitokimia, menentukan jenis komposisi fitokimia dan menentukan sebatian penanda fitokimia dalam Gynura procumbens. Kajian ini melibatkan dua faktor; masa penuaian dan kadar N, dan mengikut RCBD. Kesan-kesan terhadap faktor fisiologi dan biokimia tumbuhan telah direkodkan dalam tiga peringkat penuaian untuk memperlihatkan corak dan kualiti pertumbuhan dan kandungan fitokimia. Nitrogen memberi kesan yang jelas terhadap kandungan fitokimia (p < 0.05), dengan kesan yang signifikan terhadap faktor fisiologi dan biokimia (p < 0.01) tumbuhan. Keputusan menunjukkan bahawa 0 dan 90 kg/ha N masing-masing memberi kesan yang sangat tinggi dan paling sedikit terhadap Photo, Cond, TChlC, TCC, TPrC, TliC, TPC dan TFC.